Práticas coletivas de educação popular em saúde na Estratégia Saúde da Família - Priscilla Malta Coelho Prado (2018)
Introduction: health Education (ES) is characterized as an intervention strategy to reorganize services and should be guided by the use of pedagogical processes and techniques that aim to contribute to the improvement of the population's living and health conditions. Within the scope of the Unified Health System (SUS), ES is inherent to several practices developed, especially in Primary Health Care (PHC) through the Family Health Strategy (ESF). Despite the advances and theoretical reflections on the ES theme, one can perceive the prevalence in the development of educational actions of traditional teaching strategies. However, studies also indicate the use of non-traditional education strategies in ES activities in the ESF. In SUS, there is progress in theoretical discussions and critical reflections on health education associated with social participation and the possibilities to transform traditional ES practices into pedagogical practices that lead to overcoming situations that limit living with the maximum of quality of life through Popular Education (PE). Objective: to analyze the principles of dialogue, confrontation between knowledge and participatory democracy in the collective practices of Popular Education in the Family Health Strategy. Methodology: this is an exploratory, descriptive study of the field research type, with a qualitative approach. The study scenario consists of Basic Health Units (UBS) or intersectoral spaces belonging to the Barreiro Sanitary District of the city of Belo Horizonte, the subjects the professionals of higher level responsible for the selected educational practices. The data collection is understood by the participant observation of the collective practices of PE in the ESF selected and of interview with the professionals coordinating the observed practices. To analyze the data, we use the Content Analysis (CA). Results: 12 collective practices were identified that were grouped into categories: (1) transmitting information, promoting development and changing habits, in which practices operated with strategies that signal the participation of learning subjects and dialogue, but were conducted in the direction of transmission and reproduction of formal knowledge; (2) exchanging knowledge, stories and life experiences, in which the practices, although characterized by the openness to the participants' knowledge and experiences, did not open for problematization processes; (3) experimenting and producing collectively, in which practices, based on problematization and invention, sought to engender experimentations in different fields of problems and existence, mechanisms of subjectivation and emancipatory movements. Thus, despite the use of participatory methodologies, there were collective practices that did not favor dialogue, the confrontation between knowledge and participatory democracy. At the same time, there were advances in the incorporation into some practices of the intersubjective encounter, the confrontation between knowledge and evidence of democratic participation. Final considerations: the incorporation of the principles of PE - especially dialogue, the confrontation between knowledge and participatory democracy in some collective practices -, the commitment of professionals to innovate, combined with the use of participatory strategies can contribute to a shared construction of knowledge, allowing new awareness, productions of subjectivities and emancipation of subjects